2020
DOI: 10.1093/jamia/ocaa007
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring diabetes with multiple mobile health devices

Abstract: Objective The purpose of this study was to examine the use of multiple mobile health technologies to generate and transmit data from diverse patients with type 2 diabetes mellitus (T2DM) in between clinic visits. We examined the data to identify patterns that describe characteristics of patients for clinical insights. Methods We enrolled 60 adults with T2DM from a US healthcare system to participate in a 6-month longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
2
30
0
2
Order By: Relevance
“…Our participants submitted data on nearly 95% of days, which compares favorably to similar studies. A recent telemonitoring feasibility study with patients with type 2 diabetes mellitus found lower adherence rates compared to our trial [18]. We further found the success rate of presurvey completion to be 67% (47/70), postsurvey completion to be 70% (49/70), and pre-and postsurvey completion by the same participants to be 50% (35/70).…”
Section: Acceptability Of the Conduct Of Researchsupporting
confidence: 44%
“…Our participants submitted data on nearly 95% of days, which compares favorably to similar studies. A recent telemonitoring feasibility study with patients with type 2 diabetes mellitus found lower adherence rates compared to our trial [18]. We further found the success rate of presurvey completion to be 67% (47/70), postsurvey completion to be 70% (49/70), and pre-and postsurvey completion by the same participants to be 50% (35/70).…”
Section: Acceptability Of the Conduct Of Researchsupporting
confidence: 44%
“…We chose a qualitative descriptive study design to examine qualitative data collected as part of the Diabetes Mobile Care study; protocol details and findings (Shaw et al, 2019; Shaw et al, 2020) were published elsewhere. All research occurred at an academic medical center in the southeastern United States.…”
Section: Methodsmentioning
confidence: 99%
“…referenced the participant's use of the three mobile devices and their perceptions of the data visualizations. Questions regarding use of the devices focused on overall experience, challenges and problems, problem solving, (Burford et al, 2019;Choe et al, 2014;Lewinski et al, 2019;Lewinski et al, 2018;Shaw et al, 2019;Shaw et al, 2020;Zarghom et al, 2013) perceptions of support, and discussions with others (i.e., family, friends, clinicians). Questions about the visualizations concerned overall impressions, perception of missing data and displays, and suggestions for improvements.…”
Section: Questions and Probes Interview Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been several reports of utilizing commercially available smartwatches in studying human activities. These include generic activities such as step counts, sleep detection, and rest periods, while others include more specific activities such as eating [4], drinking [5], managing diabetes [6,7], or smoking [8]. Previous work has established the use of wristworn devices in observing and interpreting smoking behavior in laboratory settings [9][10][11][12][13] and in situ [8,14].…”
Section: Introductionmentioning
confidence: 99%